Program Kemitraan Masyarakat Posyandu Lansia RW V Kelurahan Bambankerep Kota Semarang - Ambar Dwi Erawati; Rinayati; Sri Wahyuning (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
One problem that arises from the development of health is one of increasing dependents of the productive age community towards unproductive communities. The elderly group will experience a decrease in the degree of health both naturally or caused due to disease. There is a need for an elderly coaching program that starts from pralansia is very necessary to maintain productivity. In RW V, Kelurahan Bambankerep Posyandu Lansia has not yet been formed, but there are elderly gymnastic activities that are offered once a month. So that offered solutions for the formation of Lansia Posyandu cadres so that Lansia Posyandu can be sustainable. The output of this accompanimen is that the community can check themselves to detect degenerative diseases. After 2 months of mentoring, the Posyandu for the elderly is formed and cadres of the Posyandu for the elderly can detect early degenerative diseases. The elderly found in RW V 56.1% had excessive Mass index which is a risk of hypertension, heart disease, DM, PPOP, stroke. And 52.2% of the elderly have hypertension.